Manfaat Website sebagai Media Pemasaran untuk Meningkatkan Jangkauan Pelanggan Baru pada PT. Barokah Aulia Mastur - Ar Rahman; Shinta Yuliastriy; Zikra Ababil; Gustri Efendi; April Zahmi (LPPM Universitas Ekasakti, 2025)
This research aims to develop a web-based information system to support marketing activities and improve customer outreach at PT. Barokah Aulia Mastur, a local business engaged in fish feed sales. The company currently faces limitations in its promotional methods, relying solely on conventional practices such as social media and walk-in customers, which hinders its ability to reach new markets. To address this issue, a Research and Development (R&D) method was employed, using the Waterfall model to guide the system development process through structured phases: requirements analysis, system design, implementation, testing, and maintenance. Data collection techniques included observation, interviews, literature review, and laboratory work. The resulting system was tested using black-box testing to ensure its functional reliability. The study concludes that the implementation of a web-based sales system enhances accessibility, increases promotional reach, and improves the efficiency of transaction records and customer engagement. This system provides a scalable solution for small and medium enterprises aiming to compete in the digital economy.